Evaluation of machining performance in cryogenic machining of Inconel 718 and comparison with dry and MQL machining - KAYNAK, YUSUF (SPRINGER LONDON LTD, 2014)
There has been significant work on establishing relationships between machining performance and the cutting parameters for various work materials. Recent trends in machining research show that major efforts are being made to understand the impact of various cooling/lubrication methods on machining performance and surface integrity characteristics, all aimed at improving process and product performance. This study presents the experimental results of cryogenic machining of Inconel 718, a high-temperature aerospace alloy, and comparison of its performance in dry and minimum quantity lubrication machining. Experimental data on force components, progressive tool wear parameters such as flank wear, notch wear, crater wear, cutting temperature, chip morphology, and surface roughness/topography of machined samples are presented. New findings show that cryogenic machining is a promising research direction for machining of high-temperature aerospace alloy, Inconel 718, as it offers improved machining performance in terms of reduced tool wear, temperature, and improved surface quality. It was also found that the number of nozzles in cryogenic machining plays a vital role in controlling cutting forces and power consumption in cryogenic machining of Inconel 718.
Keywords: Cryogenic machining; MQL; Machining performance; Inconel 718; PROGRESSIVE TOOL-WEAR; NICKEL-BASE; SHEAR INSTABILITY; GROOVED TOOLS; CHIP FLOW; MACHINABILITY; BEHAVIOR; ALLOYS; MECHANISMS; PREDICTION